2015
DOI: 10.1097/pas.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Myoepithelial Carcinoma of Salivary Glands

Abstract: Myoepithelial carcinoma (MECA) is an underrecognized rare tumor with a diverse clinical behavior. The histologic features of this tumor are not well characterized, much less its grading, which is controversial. The objective of this study is to provide a better characterization of MECA and its prognostic factors. A total of 48 cases were retrieved from the pathology files. The cases were subjected to a detailed histopathologic, immunohistochemical, statistical, and clinical analysis. Tumors were classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 16 publications
3
83
2
Order By: Relevance
“…Based on our series and previously reported cases fitting our inclusion criteria, thoracic MTs are tumors of adulthood, with an age range of 18-77 yrs (mean 52) in the combined data set. This is similar to myoepithelial carcinomas of the salivary gland, which have all been reported in adults with the exception of one in a 14 year-old male 6,7,28,30,31 . In contrast, approximately 10-20% of soft tissue MTs occur in the pediatric population, with several cases reported in children under 10 years of age 4,32,33 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Based on our series and previously reported cases fitting our inclusion criteria, thoracic MTs are tumors of adulthood, with an age range of 18-77 yrs (mean 52) in the combined data set. This is similar to myoepithelial carcinomas of the salivary gland, which have all been reported in adults with the exception of one in a 14 year-old male 6,7,28,30,31 . In contrast, approximately 10-20% of soft tissue MTs occur in the pediatric population, with several cases reported in children under 10 years of age 4,32,33 .…”
Section: Discussionsupporting
confidence: 83%
“…Finally, there are a number of metastatic tumors that can have overlapping morphologic and immunohistochemical features with MTs including metastatic melanoma, matrix producing carcinoma of the breast, ossifying fibromyxoid tumor (OFT), extraskeletal myxoid chondrosarcoma (EMC), clear cell sarcoma (CCS), and Ewing sarcoma. Close clinical evaluation is therefore required to exclude a metastasis, including from a salivary gland or soft tissue primary, as lung metastasis can occur several years after resection 7,31,32,41 . MT could also be confused with squamous cell carcinoma, particularly in small biopsies, because they can both express p63 and/or p40.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This article also suggested that a tumor of more than 2 cm confers poor prognosis [8]. Data from salivary gland tumors showed that the presence of necrosis and vascular invasion correlated with inferior disease-free survival [9]. Our patient presented with many adverse clinical features, including a large tumor, poor performance status, malnutrition, lactic acidosis, and pulmonary embolism.…”
Section: Discussionmentioning
confidence: 97%